Fistula Kista Duktus Tiroglosus - Ernawati, Ernawati; Murtala, Bachtiar; Kaelan, Isdiana; Muliati, Sri (Jurnal Biomedik : JBM, 2021)
Abstrack: Thyroglossal duct cyst fistula or fistula ductus thyroglossal cyst is a fistula formed from congenital masses that are most commonly found in the midline of the neck. These cysts are formed as a result of failure of involution of the thyroglossal duct. We reported a case of a 19 year old patient with a history of abscess in the neck since the patient was 3 years old. The most common incidence of thyroglossal duct cysts is in children, with the highest age being between the ages of 0-20 years, namely 52%. The occurrence of a thyroglossal duct cyst then becomes infected if it is associated since the patient was 3 years old, where the repeated throat infection process will stimulate the epithelial cells of the tract resulting in cystic degeneration, it can also be caused by clogging of the thyroglossal duct which results in a buildup of secretes to form cysts. Furthermore, if the therapy is not received properly, the repeated infection process causes cysts to form and ends up becoming fistulas. The fistulogram examination results presence of the fistula estuary from the fistula that reaches the oral cavity. After the fistelectomy operation, a visible specimen was seen to be approximately +/- 2 digits long and +/- ½ little finger wide. Furthermore, the specimen was not subjected to histopathological examination on the grounds that the cystic lesions tended to be benign, supported by a physical examination without suspicion of malignancy. The patient is discharged in good health and fully recovered because until now there have been no complaints of recurrence in the form of infection and hematomaKeywords: thyroglossal duct fistula, thyroglossal cyst. Abstrak : Thyroglossal duct cyst fistula atau fistula kista ductus tiroglosus adalah fistel yang terbentuk dari massa kongenital yang tersering ditemukan pada midline leher. Kista ini terbentuk akibat kegagalan involusi dari duktus tiroglossus.Kami melaporkan kasus pasien berusia 19 tahun riwayat absses pada leher telah dikeluhkan sejak pasien berumur 3 tahun. Insiden kista duktus tiroglosus tersering pada anak-anak, umur terbanyak antara usia 0-20 tahun yaitu 52%. Terjadinya kista duktus tiroglosus kemudian menjadi infeksi jika dikaitkan sejak pasien berumur 3 tahun, dimana proses infeksi tenggorokan yang berulang akan merangsang sel epitel traktus sehingga mengakibatkan degenerasi kistik, dapat pula diakibatkan oleh sumbatan duktus tiroglosus yang mengakibatkan terjadinya penumpukan secret sehingga membentuk kista. Selanjutnya apabila tidak mendapat terapi dengan baik,proses infeksi yang berulang menyebabkan terbentuknya kista dan berakhir menjadi fistel. Pemeriksaan fistulogram memberikan hasil adanya muara fistel dari fistel yang mencapai rongga mulut. Setelah dilakukan operasi fistelektomi, nampak specimen yang terlihat kira-kira dengan panjang +/- 2 ruas jari dengan lebar +/- ½ jari kelingking. Selanjutnya specimen tersebut tidak dilakukan pemeriksaan histopatologi dengan alasan bahwa lesi kista cenderung mengarah ke jinak, ditunjang degan pemeriksaan fisis yang tidak ada kecurigaan pada keganasan. Pasien dipulangkan dengan keadaan sehat dan sembuh sempurna karena sampai saat ini tidak ada keluhan kekambuhan berupa infeksi dan hematomKata kunci : fistula duktus tiroglosus, kista tiroglosus